Unraveling the threads of depressive symptoms: Enhancing predictions of depression among university junior students - Said El-Ashker; Abdulmajeed Alharbi; Somaya Mahmoud; Feras Al-Awad; Ahlam Alghamdi; Nouf Alaqeel; Mohammed Al-Hariri (SAGE Open Medicine)
Background: The mental burden faced by university students in their early years is not frequently reported in the literature. Objectives: The aim of this study is to investigate the prevalence and predictors of depression among preparatory (first) year university students using a predictive test developed from general health and well-being questionnaires. Methods: A cross-sectional study was conducted among university students in the eastern region of Saudi Arabia from March 2023 to June 2023. A self-administered electronic general health and well-being questionnaire was implemented. Written informed consent was obtained from the participants after explaining the study’s purposes. The questionnaire consisted of three parts. Part I described the objective of the study and maintained the confidentiality of the data, part II contained questions about demographic data, and part III contained the scales of the items to assess the physical and psychological health. Results: The findings demonstrated a significant positive correlation between depressive symptoms and both perceived stress ( r  = 0.444, p  < 0.01) and perceived burdens ( r  = 0.735, p  < 0.01). In addition, there were significant negative correlations between the depressive symptoms and gender ( r  = −0.144, p  < 0.05), economic level ( r  = −0.178, p  < 0.05), and social support ( r  = −0.312, p  < 0.01). Furthermore, the results revealed that body mass index ( b  = 0.272, t(146) = 4.636, p  < .001), perceived stress ( b  = 0.182, t(146) = 2.910, p  < 0.01), and perceived burdens ( b  = 0.593, t(146) = 9.507, p  < .001) were significant predictors of depressive symptoms among Saudi university junior students. Conclusion: Our findings emphasize the need for tailored mental health support services to address depression and its predictors, especially during critical transition periods like the early stages of university life, as early detection and intervention can lead to improved management and better control of the depression.